2016
DOI: 10.1016/j.jascer.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Al2O3 grain size on high-temperature oxidation of nano-Ni/Al2O3 composites

Abstract: a b s t r a c tTwo 5 vol% Ni/Al 2 O 3 composites with the difference in Al 2 O 3 grain size were fabricated by pulsed electric current sintering technique to investigate the influence of Al 2 O 3 grain size on oxidation behavior of the composites. Average Al 2 O 3 grain sizes of two fabricated composites were 1.1 m and 0.5 m after sintering. Oxidation tests were conducted at temperatures ranging from 1100 to 1350 • C for 1-48 h in air. A thin NiAl 2 O 4 layer was observed in exposed surface of samples after ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…As for the as‐sintered specimens, oxidation of Ni particles also took place during the high‐temperature bending tests. However, the thickness of oxidized zone of as‐sintered specimens in such conditions would be approximately 3 μm or less, according to a study reported by the authors . The formation of oxidized zone on as‐sintered specimens is therefore negligible, compared with the as‐healed ones.…”
Section: Discussionmentioning
confidence: 94%
“…As for the as‐sintered specimens, oxidation of Ni particles also took place during the high‐temperature bending tests. However, the thickness of oxidized zone of as‐sintered specimens in such conditions would be approximately 3 μm or less, according to a study reported by the authors . The formation of oxidized zone on as‐sintered specimens is therefore negligible, compared with the as‐healed ones.…”
Section: Discussionmentioning
confidence: 94%
“…The Ti 2 AlC particles within this layer do not have the stoichiometry of the starting material due to the diffusion and subsequent oxidation of Ti, Al, and/or C at the surface. Beyond this depth, XMA confirms that the MAX phase particles retain their original stoichiometry of 2:1:1 for Ti:Al:C. Although undoped fine grained alumina favors inward diffusion of oxygen, oxidation of the MAX‐Phase particles proceeds by an outward diffusion of the cations (Al 3+ and Ti 4+ ), which is not influenced by the grain size of the matrix . The depleted region is limited to about 20 μm (same as the maximum particle size), and hence alumina acts as a strong barrier against oxidation of particles embedded in the depth of the composite.…”
Section: Resultsmentioning
confidence: 82%
“…Beyond this depth, XMA confirms that the MAX phase particles retain their original stoichiometry of 2:1:1 for Ti:Al:C. Although undoped fine grained alumina favors inward diffusion of oxygen, 42,43 oxidation of the MAX-Phase particles proceeds by an outward diffusion of the cations (Al 3+ and Ti 4+ ), which is not influenced by the grain size of the matrix. 44 The depleted region is limited to about 20 lm (same as the maximum particle size), and hence alumina acts as a strong barrier against oxidation of particles embedded in the depth of the composite. The orientation of the basal planes of a particle to the surface may also influence the rate at which Al and Ti diffuse out.…”
Section: Stability Of the Dispersed Ti 2 Alc Particles In The Al 2 mentioning
confidence: 99%
“…NiO does not coexist with Al 2 O 3 , which has been discussed elsewhere. 5,8,12,14) This fact obviously indicates that the top surface layer is the NiAl 2 O 4 layer. Noticeably, the thickness of the top surface layer observed on an undoped sample was slightly higher than that of a Sr-doped one.…”
Section: Oxidation Testsmentioning
confidence: 96%